DATA MINING FOR ANALYSING TRENDS AND CUSTOMER BEHAVIOUR VIA INTERNET SEARCHES - Mioara, POPESCU (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 20 (2018): Annales Universitatis Apulensis Series Oeconomica, 2018)
The potential of analysis the web searches has been drawing attention of the scientific community for a few years. Despite the large amount of data publicly available from the internet searches, the opportunities for more advanced analysis are still relatively unexplored. The main objective of this paper is to analyse how the web searches can be used as an indicator for different marketing campaigns and strategies. The first analysis explores the possibility to measure the impact and results of the marketing campaigns by the volume of web searches from the period when the campaign was implemented. The second analysis aims to predict the customer behaviour based on the web searches, from the keywords correlation. Public data extracted from search engines has been used for both analyses together with tools used for analysis of trends and correlations of web searches.